Phytochemically Functionalized Cu and Ag Nanoparticles Embedded in MWCNTs for Enhanced Antimicrobial and Anticancer Properties - Yallappa, S.; Manjanna, J.; Dhananjaya, B. L.; Vishwanatha, U.; Ravishankar, B.; Gururaj, H.; Niranjana, P.; Hungund, B. S. (Nano-Micro Letters, 2015)
Nanomedicine is an emerging field concerned with the use of precision engineered nanomaterials, which leads to the development of novel remedial and diagnostic modalities for human use. In this study, Cu(NO3)2 and AgNO3 precursors were reduced to copper nanoparticles (CuNPs) and silver nanoparticles (AgNPs) using Terminalia arjuna bark extracts under microwave irradiation in the presence of well-dispersed multi-walled carbon nanotubes (MWCNTs) in aqueous medium. The formation of CuNPs or AgNPs and their functionalization with MWCNTs via bioactive molecules of plant extract were evidenced from UV–Vis spectra, XRD, FTIR, FESEM, EDX, and TEM images. The phytochemically functionalized Cu-MWCNTs and Ag-MWCNTs nanomaterials showed enhanced biocide activity, and the inhibitory activity for bacteria was higher than that of fungus. Furthermore, these biohybrid nanomaterials are non-toxic to normal epithelial cells (Vero), whereas they are highly toxic for tested human cancer cells of MDA-MB-231, HeLa, SiHa, and Hep-G2. The cell viability was found to decrease with the increasing dose from 10 to 50 µg mL−1, as well as incubation time from 24 to 72 h. For instance, the cell viability was found to be 91 % for normal Vero cells and 76 % for cancer cells for lower dose of 10 µg mL−1.